PERAN GANDA PEREMPUAN DALAM USAHATANI TOMAT DI DESA TARAITAK SATU KECAMATAN LANGOWAN UTARA KABUPATEN MINAHASA - Vialli Erick Wowiling; Jenny ., Baroleh; Jean Fanny Junita Timban (Sam Ratulangi University, 2019)
This study aims to determine the role of women in the stages of work on tomato farming and the time allocation in tomato farming and in household activities. This research was conducted for 6 months from November 2016 to May 2017 in Taraitak Satu Village, Langowan Utara District, Minahasa Regency. The data used in this study consisted of primary data obtained through interviews and observations on 20 women farmers who were deliberately selected by criteria of having a husband and working not as a tomato farmer. Secondary data was obtained from the Taraitak Satu Village Office, Unsrat Agricultural Library, the Internet through google searching in the form of a thesis from another university. Data analyzed using qualitative and quantitative analysis. Based on the results of the study concluded the stages of work involving women on tomato farming, namely the stage of seed preparation, land clearing, planting and making planting holes, planting, mulching, maintenance - including watering, weeding, fertilizing, controlling pests and diseases or spraying of pesticide, trimming and binding - , harvesting, and post-harvesting. The most dominant time allocation of female labor is at the maintenance stage except spraying drugs that are not carried out by women. Maintenance activities are carried out by women because according to the local community's views women are more diligent than men in this process namely watering, weeding, fertilizing, pruning and binding. The highest outpouring of women's work time in tomato farming is in maintenance activities, especially in binding and pruning activities, which requires 2 days per harvest where the period of 1 harvest is 3 months 2 weeks. In household activities: women with families devote time per day to work for income (tomato farming) an average of 8.3 hours per day while for housework time is 4.58 and for other activities such as worship is 4.2 hours per week. Women in the research location played a dual role as breadwinners (taking care of farming tomatoes) and at the same time as housewives who have to prepare their family's needs before going to take care of tomatoes.*eprm*